Molecular Diversity Analysis of Katokkon Chili (Capsicum annum var. chinense) Based on Inter Simple Sequence Repeat (ISSR) Markers - Al Amanah, Hafizhah; Sjahril, Rinaldi; Haring, Feranita; Larekeng, Siti Halimah (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
There are numerous kinds of chilies, and many have a specialty and specific growing location, such as the katokkon chili, which is specific to Toraja Highland, South Sulawesi Province, Indonesia. This small bell-chili pepper-shaped chili has a distinctive capsicum aroma and a short burning sensation of hot chili's strong spicy taste. This research aims to study the relationship of the genetic kinship of katokkon chili from Toraja and its surrounding regency (Enrekang and Mamasa regencies) using ISSR molecular markers, which are expected to be used as basic information in genetic resource management. Inter Simple Sequences Repeat (ISSR) markers are used for the molecular analysis of 26 katokkon accessions. The result shows that katokkon chili analyzed have a relatively high heterozygosity value of 0.488. The average heterozygosity value is 0.5. Hence, the genetic diversity in these districts is comparatively high. The katokkon chili accession is grouped into three main clusters, each comprising various samples. Only clusters II and III have a close relationship. Information on the genetic diversity based on ISSR can be used as a molecular marker to support further research on the breeding and development of katokkon chili plants and their accession.